Analysis of students' mathematical reasoning difficulties in solving systems of linear equations in two variables - Novita Dwi Lestari; Nurhanurawati; Wayan Rumite (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
The purpose of this study was to describe students' mathematical reasoning difficulties in solving problems involving systems of linear equations in two variables. This research employed a mixed-methods design with an explanatory sequential approach. The participants were 31 eighth-grade students in Class VIII-C at SMP Negeri 14 Bandar Lampung. Data were collected through tests and interviews. The test, consisting of four essay-type questions, was administered to all 31 students, while interviews were conducted with two selected students. The instruments used included a written test and an interview guide. Data analysis was carried out in two stages: descriptive statistical analysis was used for the quantitative data, and the Miles and Huberman model (data reduction, data display, and conclusion drawing) was applied for the qualitative data. The results showed that the average percentage of students' mathematical reasoning difficulties was 54.91%. The stages with the highest levels of difficulty were performing mathematical manipulations (58.33%) and drawing conclusions (76.34%). The analysis revealed that students struggled with algebraic operations and basic calculations when solving systems of linear equations in two variables. Furthermore, the interviews indicated that some students failed to provide final answers either because they had difficulty interpreting the results within the problem context or simply forgot to write them down.